Internal-wave-induced dissipation rates in the Weddell Sea Bottom Water gravity current - O. Pinner; F. Pollmann; M. Janout; G. Voet; T. Kanzow; T. Kanzow (Ocean Science)
This study investigates the role of wave-induced turbulence in the dynamics of the Weddell Sea Bottom Water gravity current. The current transports dense water from its formation sites on the shelf to the deep sea and is a crucial component of the Southern Ocean overturning circulation. The analysis is based on velocity records from a mooring array deployed across the continental slope between January 2017 and January 2019 as well as vertical profiles of temperature and salinity measured on various ship expeditions on a transect along the array. Previous studies suggest that internal waves may play a crucial role in driving turbulence within gravity currents; however, this influence has not been quantitatively assessed. To quantify the contribution of internal waves to turbulence in this particular gravity current along the continental slope, we employ three independent methods for estimating dissipation rates. First, we use a Thorpe scale approach to compute total, process-independent dissipation rates from density inversions in density profiles. Second, we apply the fine-structure parameterization to estimate wave-induced dissipation rates from vertical profiles of strain, calculated from temperature and salinity profiles. Third, we estimate wave energy levels from moored velocity time series and deduce wave-induced dissipation rates by applying a formulation that is at the heart of the fine-structure parameterization. Turbulence is highest at the shelf break and decreases towards the deep sea, in line with decreasing strength of wave-induced turbulence. We observe a two-layer structure of the gravity current, a strongly turbulent bottom layer about 60–80 m thick, and an upper, more quiescent interfacial layer. In the interfacial layer, internal waves induce an important part of the dissipation rate and therefore drive entrainment of warmer upper water into the gravity current. A precise quantification of the contribution is complicated by large method uncertainties. A comparison with turbulence measurements up- and downstream of our study site indicates that the processes dominating turbulence generation may depend on the location along the Weddell Sea Bottom Water gravity current: on the shelf trapped waves are most important, on the continental slope breaking internal waves dominate, and in the basin symmetric instability is likely the main driver of turbulence.